A multi-wavelength view of distinct accretion regimes in the pulsating ultraluminous X-ray source NGC 1313 X-2 - Sathyaprakash Rajath; Roberts Timothy P.; Grisè Fabien; Kaaret Philip; Ambrosi Elena; Done Christine; Gladstone Jeanette C.; Kajava Jari J. E.; Soria Roberto; Zampieri Luca (OXFORD UNIV PRESS, 2022)
NGC 1313 X-2 is one of the few known pulsating ultraluminous X-ray sources (PULXs), and so is thought to contain a neutron star that accretes at highly super-Eddington rates. However, the physics of this accretion remains to be determined. Here, we report the results of two simultaneous XMM-Newton and HST observations of this PULX taken to observe two distinct X-ray behaviours as defined from its Swift light curve. We find that the X-ray spectrum of the PULX is best described by the hard ultraluminous regime during the observation taken in the lower flux, lower variability amplitude behaviour; its spectrum changes to a broadened disc during the higher flux, higher variability amplitude epoch. However, we see no accompanying changes in the optical/UV fluxes, with the only difference being a reduction in flux in the near-infrared (NIR) as the X-ray flux increased. We attempt to fit irradiation models to explain the UV/optical/IR fluxes but they fail to provide meaningful constraints. Instead, a physical model for the system leads us to conclude that the optical light is dominated by a companion O/B star, albeit with an IR excess that may be indicative of a jet. We discuss how these results may be consistent with the precession of the inner regions of the accretion disc leading to changes in the observed X-ray properties, but not the optical, and whether we should expect to observe reprocessed emission from ULXs.